Spatiotemporal patterns and dynamic mechanisms of ecosystem services in the coastal zone of China - Chen, Mingbao; Li, Maolin; Wang, Ping (Frontiers in Environmental Science, 2025)
Ecosystem services (ESs) are a key component of social-ecological system (SES). Exploring the spatial processes of coastal ESs is of great significance for promoting the high-quality development of coastal zones. This study investigates the spatial patterns of ESs and their interrelationships, identifies the key driving mechanisms, and subsequently offers sustainable management strategies. The major results reveal that (1) ESs exhibit a fluctuating growth trend (k = 0.017, R2 = 0.175) from 2000 to 2022, but their synergistic effects are gradually weakening; Spatially, ESs show a pattern of higher levels in the south and lower levels in the north, with a significant north-south disparity; In the future, ESs exhibit a slight upward trend (mean Hurst = 0.516), with the spatial processes in the southern region being stronger than those in the northern region. (2) ESs are more strongly influenced by social factors and less affected by natural factors. Natural factors have a weak positive influence on ESs, while the opposite is true for social factors; Social factors exert a stronger nonlinear mechanism on ESs than natural factors. (3) The spatial processes of ESs demonstrate a pronounced aggregation pattern, which can serve as a basis for spatial partitioning. As a result, we integrate local realities and governance knowledge into spatial planning to support the sustainable development of SES.